Produções de sentido de consumo e trabalho nas narrativas de superação da telenovela viver a vida - Campos Junior, Walfredo Ribeiro de (2013)
This study aims to analyze the representations of work and consumption present in the narratives of overcoming bodily traumas, which were part of the collective of life stories of "ordinary people" included at the end of each chapter of the soap opera Viver a Vida (Rede Globo, 2010) and made available on the website Portal da Superação. The theoretical framework that supports this research is based in discussions about the relationship between communication, work and consumption, as well as sociocultural and media contexts on which such statements were made. The methodology applied to the research is the analysis of the discursive approach, combined with the visual analysis and theories of narrative.